KNOWLEDGE AND ATTITUDES OF POLICE AND MEDICAL DOCTORS IN CENTRAL LAMPUNG REGENCY REGARDING ALCOHOL LEVEL TEST FOR MOTOR VEHICLE DRIVERS - WIGUNA, I PUTU SUWARTAMA; Syukriani, Yoni Fuadah; Huspa, Fitri Agustina (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Based on data from the Global Status Report on Road Safety published by the World Health Organization in 2018 and 2023, traffic accidents are one of the factors causing death in the world. One of the influencing factors is alcohol because it can interfere with concentration while driving. Various countries have tried to reduce the number of traffic accidents by checking drivers’ alcohol levels. Indonesia is one of the countries that has not implemented the test routinely, while the number of traffic accidents is still relatively high. For example, traffic accident victims in Lampung Province have increased between 2021 and 2022, and Central Lampung Regency ranks 2nd highest in traffic accidents in Lampung Province. Efforts to check alcohol levels require the involvement of police agencies and hospitals, including police officers and doctors. This research describes the knowledge, attitudes, and behaviour of police officers and doctors in Central Lampung Regency regarding alcohol level tests in drivers who have experienced traffic accidents. The research used an explanatory sequential mixed method design. Quantitative data regarding knowledge and attitudes were collected through questionnaires (n=77, 36 doctors, 41 police officers). The convenience sampling approach was used as the sampling method, then analyzed using SPSS ver.27. Data analysis was carried out using univariate, bivariate (Spearman test, Mann-Whitney test, Chi-square and Fisher exact tests), and multivariate logistic regression tests. Qualitative data to explain the knowledge, attitudes, and behaviour were collected through interviews through purposive sampling. The results showed that there were significant differences in knowledge, attitudes and behaviour between police and doctors (p<0,001); there is a weak correlation between knowledge and attitudes and behaviour of police and doctors (r=0,399). Age, length of service, gender, education, and occupation significantly correlate with the knowledge, attitudes and behaviour of police and doctors (p<0,05). The age factor has the most dominant relationship with knowledge (OR 3,4; p=0,02) in police and doctors. Qualitative data explained that young doctors have better knowledge, as well as more positive attitudes and behaviour towards alcohol level tests, compared to that of the police and older doctors. It can be concluded that there are significant differences between police and doctors in knowledge, attitudes and behaviour towards alcohol level tests of drivers involved in traffic accidents. It is suggested that the alcohol testing policy for drivers needs to be preceded by education for police and doctors using a different approach.